Membangun Kinerja Pemasaran Usaha Mikro Kecil dan Menengah Mebel Di Kabupaten Jepara (Studi Kasus Pada UMKM Mebel di Kabupaten Jepara) - Prapriani, Yanu Arika; Sugiarto Ph, Yohanes (Diponegoro Journal of Management, 2014)
Micro, Small and Medium Enterprises (MSME) constitute the largest segment of the Indonesian national economic actors. MSME play an important role in the Indonesian economy, because MSME are able to absorb the productive labor available. One of the MSME that help the Indonesian economy are MSME furniture in Jepara. Furniture is one of the largest exporters of actors that can help the Indonesian economy. Variables that can help build marketing performance is Market Orientation, Orientation Entrepreneurship and Innovation.The population in this study is the owner of MSME furniture in Jepara. Samples were taken as many as 83 respondents. Data was collected using a survey method through questionnaires filled out by the owner of the furniture. Then the data were analyzed using regression analysis. Calculation of moderating variables using Sobel Test. Based on the research results, the regression equation: Y 1 = 0.367 X1 + 0.324 X2. And Y2 = 0.401X1 + 0.455 X2 + 0.671 Y1. Based on statistical data analysis, the indicators in this study are valid and variables are reliable. The variable that has the most impact is variable Market Orientation. Sobel test results of a calculation produces the effect of each variable through the mediating variables of innovation.